IMPLEMENTASI SISTEM INFORMASI PEMESANAN MAKANAN PADA CAFE OZORA BERBASIS WEB - Fidelis, Ricky; Imanuel Ndaumanu , Ricky; Kartini, Paskalia (LPPM Universitas Widya Dharma Pontianak, 2024)
Cafe Ozora is located on Jl. Ampera, pal IX, Sungai Jawi, Kec. Pontianak city, West Kalimantan. The goal of Cafe Ozora is to provide a unique cafe experience by serving high-quality coffee, delicious snacks, and a comfortable atmosphere for customers and strive to ensure that the cafe is not only a place to enjoy coffee, but also a community center where people can gather, work, and relax. As time goes by, Cafe Ozora understands that modern customers want convenience in ordering food. Therefore, the author initiated to create a web-based ordering application, where customers can easily browse the menu, order food, and even pay in cash and online. The food ordering application can also help Cafe Ozora improve their operational efficiency. With an order management system integrated with a MySQL database, cafe managers can track orders better, manage inventory, and estimate demand more accurately. The software for managing orders at the cafe is a web-based application that utilizes gadgets as tools. This application will be designed with an attractive and user-friendly interface. Through this interface, users can access the list of menus available at the cafe. It is hoped that this web-based cafe management software will help cafe owners, employees, and customers to interact more easily. Keywords: Designing, Website,QR Code, Order